Transcranial Direct Current Stimulation as an Add-on Treatment to Cognitive-Behavior Therapy in First Episode Drug-Naïve Major Depression Patients: The ESAP Study Protocol - Carvalho, Sandra; Gonçalves, Óscar F.; Brunoni, André R.; Fernandes-Gonçalves, Ana; Fregni, Felipe; Leite, Jorge (Frontiers in Psychiatry, 2020)
Background: Major Depressive Disorder (MDD) affects more than 264 million people worldwide. Current treatments include the use of psychotherapy and/or drugs, however ~30% of patients either do not respond to these treatments, or do not tolerate the side effects associated to the use of pharmacological interventions. Thus, it is important to study non-pharmacological interventions targeting mechanisms not directly involved with the regulation of neurotransmitters. Several studies demonstrated that transcranial Direct Current Stimulation (tDCS) can be effective for symptoms relief in MDD. However, tDCS seems to have a better effect when used as an add-on treatment to other interventions. Methods/Design: This is a study protocol for a parallel, randomized, triple-blind, sham-controlled clinical trial in which a total of 90 drug-naïve, first-episode MDD patients (45 per arm) will be randomized to one of two groups to receive a 6-weeks of CBT combined with either active or sham tDCS to the dorsolateral prefrontal cortex (DLPFC). The primary outcome will depressive symptoms improvement as assessed by the Montgomery-Asberg Depression Rating Scale (MADRS) at 6-weeks. The secondary aim is to test whether CBT combined with tDCS can engage the proposed mechanistic target of restoring the prefrontal imbalance and connectivity through the bilateral modulation of the DLPFC, as assessed by changes over resting-state and emotional task eliciting EEG. Discussion: This study evaluates the synergetic clinical effects of CBT and tDCS in the first episode, drug-naïve, patients with MDD. First episode MDD patients provide an interesting opportunity, as their brains were not changed by the pharmacological treatments, by the time course, or by the recurrence of MDD episodes (and other comorbidities). Trial Registration: This study is registered with the United States National Library of Medicine Clinical Trials Registry (NCT03548545). Registered June 7, 2018, clinicaltrials.gov/ct2/show/NCT03548545. Protocol Version 1.